Effect of the Social Environment on Spring Migration Timing of a Songbird - Deakin, Jessica E.; Guglielmo, Christopher G.; Morbey, Yolanda E. (Frontiers in Ecology and Evolution, 2021)
The influence of the social environment on the timing of the annual cycle is poorly understood. Seasonally migratory birds are under pressure to accurately time their spring migration, and throughout the annual cycle, they may experience variability of the local sex-ratio. A population-level male-biased sex ratio is predicted to advance spring migration timing in males and is attributed to the increased intra-specific competition for access to females and/or breeding territories. The present study had two goals. First, to develop a method that utilizes digitally coded radio-transmitters to quantify the activity of flocked individuals in captivity. Second, to use this method to test the hypothesis that the social environment influences the spring migration traits of male yellow-rumped warblers (Setophaga coronata coronata). To accomplish this, birds were captured in the fall in Long Point, Ontario, and transferred to the Advanced Facility for Avian Research, London, Ontario. In the winter, they were assigned to a slightly male- or female-biased treatment and housed in flocks in large free-flight rooms. Throughout the experimental period, we took body mass measurements and standardized photos to monitor body condition and molt progression. To measure locomotor activity, the birds were outfitted with digitally-coded radio-transmitters in April and photo-triggered to enter a migratory phenotype. The tagged birds were released at their capture site in May and the Motus Wildlife Tracking System was used to determine stopover departure timing and migratory movements. Sex ratio did not influence body mass or molt progression. However, males from the male-biased treatment had significantly less locomotor movement than those from the female-biased treatment. Additionally, a lower proportion of males from the male-biased treatment initiated migratory restlessness, an indicator of the urge to migrate. Overall, these findings suggest that the social environment can influence behaviour of songbirds, but do not support the hypothesis that a male-biased sex ratio accelerates migration.